Effect of platelet concentrate prepared by different methods on the healing of full‐thickness skin defects. (22nd August 2022) - Huang, Liwen; Dong, Yunqing; Li, Changhui; Han, Sheng; Cheng, Biao
Abstract: Background: Platelet‐rich plasma and concentrated growth factors have been widely utilized in tissue regeneration. However, very few studies have focused on comparing the merits of these two materials in skin repair. Aims: We aim to compare the wound healing effects of four platelet concentrates. Methods: Auto‐platelet‐rich plasma, artificial platelet‐rich plasma, concentrated growth factors in a liquid phase, and a gel phase were prepared, and a full‐thickness skin defect model of mice was made. The skin defects were treated with normal saline as a control and also the four kinds of platelet concentrates mentioned above, respectively. Wound size was measured and calculated on days 3, 5, 7, and 10, with histological analysis performed. Results: All four platelet concentrates accelerated wound healing in mice. Interleukin‐1β (IL‐1β) and tumor necrosis factor (TNF‐α) in concentrated growth factors in a liquid phase, a gel phase, and artificial platelet‐rich plasma groups were significantly lower than those in the control group; and vascular endothelial growth factor (VEGF) and CD34 were significantly higher than those in the control group and auto‐platelet‐rich plasma group. Conclusions: All four platelet concentrates appear to promote wound healing. Compared with auto‐platelet‐rich plasma, concentrated growth factors in a liquid phase and in a gel phase, and artificial platelet‐rich plasma seem to have more substantial effects in promoting angiogenesis, epithelialization, and reducing inflammation, thus promoting a stronger effect on wound healing.